Cubic Bi2O3-Based Electrochemical Nitric Oxide Sensor Using Double Perovskite Oxide Electrodes. Issue 11 (1st November 2022) - Bhardwaj, Aman; Bae, Hohan; Mathur, Lakshya; Mathur, Sanjay; Song, Sun-Ju
Abstract : For achieving a sustainable energy future, energy consumption through renewable sources needs to be maximized and greenhouse emissions should be radically reduced. Automotive exhausts sharing the largest global NOX emissions must meet regulated standards by after-treatment systems (ATS) equipped with smart electronic feedback loops through on-board NOX monitoring. Herein, we demonstrate an efficient (Dy, W) co-doped Bi2 O3 -based electrochemical sensing architecture equipped with Ln2 NiMnO6 double perovskite oxides (DPOs) as electrode materials for selective nitric oxides (NO) detection. The sensor configuration facilitates operation in a wide temperature range (325 °C–500 °C) with high sensitivity of 50 mV/decade, a response time below 60 sec. and detection abilities as low as 200 ppb. While investigating the impact of rare-Earth cations, a predominant Ni 3+ –O–Mn 3+ interaction and acquisition of optimal eg 1 electron configuration of transition metal atoms in La2 NiMnO6 was found responsible for improved electrocatalytic and redox chemical activity that substantiates the sensing behavior. The study carefully scrutinizes the sensing mechanism to abide by the mixed-potential model. Moreover, the durability assessed over a month of operation supported the applicability of presented sensing elements in on-board NOX monitoring systems.